A comonotonic theorem for backward stochastic differential equations in L^p and its applications - Zong, Z.-J. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study backward stochastic differential equations (BSDEs) under weak assumptions on the data. We obtain a comonotonic theorem for BSDEs in L^p,1, 1 < p ≤ 2. As applications of this theorem, we study the relation between Choquet expectations and minimax expectations and the relation between Choquet expectations and generalized Peng’s g-expectations. These results generalize the known results of Chen et al.